PENGARUH KEDISIPLINAN BELAJAR DAN KEMANDIRIAN BELAJAR TERHADAP KREATIVITAS BELAJAR SISWA DI SMK MULTI MEKANIK MASMUR PEKANBARU - Frisilla Agra Izzati; Gimin Gimin; Henny Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of learning discipline and learning independence on the learning creativity of students at the Multi Mechanics Vocational School in Pekanbaru. The study was conducted on a population of 44 students from class X and XI accounting of Multi Mechanics Vocational School Masmur Pekanbaru. The type of data used in this study is primary data in the form of data about learning discipline, learning independence and learning creativity. Data were analyzed using descriptive analysis and multiple linear regression. Descriptive analysis results indicate discipline of learning, learning independence and learning creativity are still in the low category. Multiple linear regression analysis found that learning discipline and learning independence had a positive effect on learning creativity with a contribution of 58.3%. The results of the study found that there was a positive influence between learning discipline on learning creativity by 0.247 and there was a positive influence between learning independence on student learning creativity by 0.524. The variable that has greater influence on creativity is learning independence. The recommendations in this study so that student learning creativity can be improved. There are several ways needed to improve learning creativity, namely by increasing learning independence and increasing learning independence in the learning process.Key Words: Discipline, Independence, Learning creativity